Mind the Gap: Reach and Mechanical Diversity of Searcher Shoots in Climbing Plants - Hattermann, Tom; Petit-Bagnard, Laureline; Heinz, Christine; Heuret, Patrick; Rowe, Nick P. (Frontiers in Forests and Global Change, 2022)
Climbing plants need to reach supports and position their leaves for light capture. Vines and lianas develop a large diversity of self-supporting shoots among diverse species and different kinds of attachment. A searcher’s reach is a crucial trait for colonising supports in complex three-dimensional spaces. We explore the reach capacity and diversity of searcher shoots among representative temperate and tropical climbing plants. We investigate the overall range of variation between short- and long-reach searchers; the mechanical and anatomical organisations underlying reach capacities; how searcher architectures are linked to different climbing strategies such as stem twining, tendril climbing, root climbing, and branch-angle-hook climbing. We investigated reach and mechanical and anatomical organisations (stem rigidity and stiffness, stem and tissue geometry) in 29 climbing plant species from temperate and tropical habitats. Searchers show a wide range of maximal reach per species from 0.1 to 2.5 m. Flexural rigidity (EI) at the base of searchers increased with reach length; overall this increase was proportional although some longest-reaching shoots develop proportionally thinner searcher bases with higher stiffness [structural Young’s modulus (Estr)] than shorter-reach shoots. Bases of short-reach searchers rely more on primary tissues compared to long-reach shoots, which rely more on wood production. We identified different mechanical architectures for a given reach capacity across all species. These are linked to different kinds of attachment mechanisms, support foraging, and possibly leaf display. Plants attaching by twining of the main stem showed a wide range of reach capacity. They also developed lighter, more slender, less rigid, but generally relatively stiff (higher Estr) shoots compared with tendril climbers and branch-angle-hook climbers. Differences in the mechanical architecture of searcher shoots in climbing plants are informative for understanding how diverse climbing plant species explore and colonise different kinds of three-dimensional spaces. This is a key feature that distinguishes different habitat preferences. We discuss how such knowledge is not only important for understanding functional biology and ecology of climbing plants but is also of interest for developing new technologies in soft robotics that mimic climbing plants that can navigate through unstructured environments.